“Bort med den uværdige Higen efter Nøjagtighed”: En læsning af Sophus Claussens “Udløbet i Uendeligheden” - Sohl Jessen, Mads (Danske Studier, 2024)
While Sophus Claussen’s poem “Udløbet i Uendeligheden” is regarded as one of his most important poems, it has not been the subject of much in-depth analysis. Claussen made a substantial draft of the poem already in 1896, but he did not publish the final revised version of the poem until 1930 when it appeared in his last collection of poetry Hvededynger. In this study I suggest that a close reading of the first version, which differs from the final one, is crucial in order to understand the argument Claussen is making in the poem. More specifically I argue that the poem’s argument should be regarded as a refutation of the poetics of Claussen’s canonical poem “Ekbátana” from 1895. In “Ekbátana” Claussen posits his sojourn in Paris in the early 1890s as the place and period of time for his poetical incarnation as a major symbolist poet, but in “Udløbet i Uendeligheden” Claussen relates his symbolist breakthrough to his childhood years in Falster and the experience at nighttime of the natural surroundings at Guldborgsund.